A study of parameters relationship to backcutting phenomena during high speed end milling of AISI H13 - Adesta, Erry Yulian Triblas; Mohd Ali, Afifah; Agusman, Delvis; Muhammad, Riza; Suprianto, Mohamad Yuhan (Science Publications, 2010)
Problem Statement: In die and mold industries, surface roughness of the dies and molds produced will determined the end product quality. Therefore, the desired finish surface was specified and the appropriate processes were selected to reach the required quality. Among many contributors to surface quality problem, backcutting is one of the factors influencing the surface roughness. Approach: The aim for current research was to study the backcutting phenomena and their effect to the surface roughness of work material, AISI H13 with hardness of 48 HRC during high speed end milling. Machining performed on the Vertical Milling Centre (VMC) high cutting speed from 150-250 m/min, feed rate 0.005-0.15 mm/tooth and depth of cut 0.1-0.5mm. The analysis and observations of the backcutting phenomena are done by using optical surface roughness machines. Results: The result shown that pattern of surface roughness was not sufficient enough to compare between the surface with backcutting and without backcutting phenomena were seen mostly in combination of medium to high speed and medium to high feedrate. Conclusion/Recommendations: Futher research is needed with incrimination of experiments and adjustments of parameters.